New records of terrestrial pteridophytes in Genting Highlands, Pahang, Malaysia - Ahmad Bedawi, Salifah Hasanah; Go, Rusea; Mustafa, Muskhazli (Universiti Putra Malaysia Press, 2009)
Genting Highlands is the common name for a general area including a group of summits around Gunung Ulu Kali and their ridges. Located at the border between the State of Selangor to the west and Pahang to the east, the entire area was a virgin forest until 1967, when the roadwork was begun. To date, there have been fragmented reports in botanical studies in Genting Highlands. The previous works by Ridley, Holttum, Parris, Latiff and Piggott are lacking on studies, specially the ones focusing on pteridophytes in selected study sites. Fieldworks were conducted to assess the species list of terrestrial pteridophyes on April and September of 2005. From these expeditions, a total of 32 species of terrestrial pteridophytes were collected from two sites in Genting Highlands with 21 species being new records for the area. Two species namely, Diplazium subintegrum and Taenitis dimorpha, were found to be endemic to Peninsular Malaysia.